The influence of NPF, FDR, and BOPO on ROA at BPRS Amanah Rabbaniah Banjaran - Nur’aeni Nur’aeni; Finda Nur Wahyuni (Research Collaboration Community (RCC), 2023)
This study aims to determine how the influence of NPF, FDR, BOPO on ROA at BPRS Amanah Rabbaniah Banjaran partially or simultaneously. This type of research is quantitative associative with secondary data types and uses data collection techniques in the form of documentation and literature study. While the sampling technique is non-probability sampling, with a population of all quarterly financial reports of BPRS Amanah Rabbaniah with a sample of quarterly financial statements of BPRS Amanah Rabbaniah for the period 2017-2021. The result of this study is that there is no effect between NPF on ROA where tcount < ttable (-0.9565 < 2.109). There is a significant but negative effect between FDR on ROA where tcount > ttable (-2.1309 > 2.109). There is an effect of BOPO on ROA where tcount > ttable (4,798 > 2,109). and simultaneously there is a significant effect between NPF, FDR and BOPO on ROA at BPRS Amanah Rabbaniah Banjaran where Fcount > Ftable (11.48, > 2.64).